Lipid-lowering treatment in peripheral artery disease. (April 2018) - Katsiki, Niki; Giannoukas, Athanasios D; Athyros, Vasilios G; Mikhailidis, Dimitri P
Highlights: Peripheral artery disease (PAD) is characterized by increased cardiovascular risk. Statins remain the first-line lipid-lowering therapy to treat PAD patients. Statins decrease all-cause and cardiovascular death in PAD patients. The role of other lipid-lowering drugs in PAD patients requires further research. Abstract : Peripheral artery disease (PAD) is characterized by increased cardiovascular (CV) risk, limb morbidity and all-cause mortality. According to the current guidelines (2016) of the American Heart Association/American College of Cardiology on the management of PAD patients, statin therapy is recommended for PAD patients in order to treat dyslipidemia and reduce CV risk. The present narrative review discusses the use of statins and other lipid-lowering drugs such as ezetimibe, fibrates, niacin, anacetrapib and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors in PAD patients in terms of both CV and limb outcomes. The clinical implications of hypolipidemic drug therapy in special patient populations including those with metabolic syndrome, non-alcoholic fatty liver disease, chronic kidney disease and type 2 diabetes mellitus, which may frequently co-exist with PAD, are also considered.